Government of Tanzania includes joint village land use planning (JVLUP) in national manual on participatory village land use planning - CGIAR Research Program on Livestock (2021)
The Government of Tanzania released a revised edition of their manual for participatory village land use planning, which promotes the national undertaking of joint village land use planning (JVLUP).